THE RELATIONSHIP OF HUSBAND SUPPORT AND WOMEN’S WILLING FOR INSTALLATION OF IUD CONTRACEPTION (INTRAUTERINE DEVICE) IN STAGE IV - Ika Setiawati; Titik Suhartini; Mega Silvian Natalia (NHM PRESS, 2023)
The Family Planning Service (KB) program in Indonesia is experiencing a stagnant situation which is marked by the lack of increasing several indicators of family planning services, namely the number of participation in KB (Contraceptive Prevalence Rate = CPR) and unmet need. These two indicators are additional indicators in the fifth goal of the Millennium Development Goals (MDGs) 2015. This study aims to analyze the relationship between husband's support and willingness to give birth for the installation of an IUD (Intra Uterine Device) contraceptive during the fourth stage of labor in the Tegalsiwalan Health Center Work Area, Probolinggo Regency. This research is a quantitative research design with a correlational design using a cross sectional study approach with 45 respondents using accidental sampling technique. Data collection includes coding, editing and tabulating, then analyzed manually and on a computer using the Wilcoxon test. Based on the data it can be seen that of the 45 respondents, most of the husband's support was lacking, 24 respondents (53.3%) including the willingness of maternity mothers who were willing to insert an IUD, a total of 9 respondents (20%) and 15 respondents (33.3) who were not willing. %). obtained P Value : 0.000 and a = 0.05 means r < a, so H0 is rejected and Ha is accepted, and there is a relationship between husband's support and willingness of the mother to give birth for the installation of an IUD (Intra Uterine Device) contraceptive during the fourth stage of labor in the Tegalsiwalan Health Center Work Area. Probolinggo Regency. It is hoped that many sources of support can be obtained by someone from the environment and surroundings, therefore it is necessary to know how many sources of husband's support are effective for individuals who need it. The husband's source of support is an important aspect to improve reproductive health, so it needs to be known and understood.